PENGARUH METODE PELATIHAN DAN SIMULASI TERHADAP PENGAJARAN GURU-GURU BAHASA ASING SMK PARIWISATA - NI Luh Sukanadi; I Ketut Wardana (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
The main issues of English and Japanese teachers who teach at SMK Tourism Mengwi Tani and SMK PGRI 3 Badung is the essence of mastery of foreign languages, the empowerment of learners and the carrying capacity of instructional media. The purpose of this program is to empower foreign language teachers in improving the quality of teaching. To achieve the target outcome, the method of science applied is transfer technology in the form of workshop, simulation, and, mentoring. Implementation of the program has been implemented in the form of three-day workshop on the application of bihavioristik theory, humanism, cognitive, CTL and multimedia-based foreign language teaching. This activity involves 15 foreign language teachers from two schools. Implementation of pre experimental methods to determine the effect of the action given by comparing the conditions and quantities before the action is given. The model used is a single subject pretest subject, without a control group. Based on the result of paired sample t test analysis using SPSS 17 for Windows software obtained p = 0.000 (t = -8.386, df = 14) <α = 0.05 indicates that Ho is rejected and H1 accepted. While data analysis of pretest and postes, t-observed for df 14 on t-table is 2.03 with a significant level of 0.05. This shows that t-observed 4.36 is bigger than t-table, ie: 2.03. It can be concluded that the workshop on communicative teaching approaches has a significant influence on the ability of foreign language teachers in both partner SMK Tourism schools. From this activity, efforts to strengthen, empower and improve the skills of these teachers can be an inspiration for improving the ability of learners in using foreign language.